Analysis of the Impact of Fiscal and Monetary Policy on Indonesian Macroeconomic Performance With Model Structural Vector Autoregression (SVAR) - setiawan, heru (Jurnal Ilmu Ekonomi Terapan, 2018)
In this paper we attempt to analyze effects of fiscal and monetary policy on output, inflation and interest rates in Indonesia using Structural Vector Autoregression (SVAR) for the period 2001:1 – 2017:3. We follow Blanchard and Perotti (2002) methodology to identify the structural shocks and analyze the transmission mechanisms of fiscal and monetary policy on economic activity. The estimation results show that expansionary fiscal policy through increase in government spending are found to have relatively small (though positive) effect on output. Moreover, the increase in government spending lead to relatively higher inflation and interest rate. A tax shock, which is mean the contractionary fiscal policy, give negative effect on the output but turn into positive effect after one year. A shock in interest rate follow by decrease in inflation, which is accordance with Taylor Rule. Overall, the empirical result indicate the less potent fiscal policy to stimulate output in short-time period while putting upward pressure on inflation and nominal interest rate.